Soil Enzyme Activities and Their Relationships With Soil C, N, and P in Peatlands From Different Types of Permafrost Regions, Northeast China - Liu, Chao; Song, Yanyu; Dong, Xingfeng; Wang, Xianwei; Ma, Xiuyan; Zhao, Guangying; Zang, Shuying (Frontiers in Environmental Science, 2021)
Peatland is a key component of terrestrial ecosystems in permafrost regions and have important effects on climate warming. Soil enzymes are involved in biogeochemical cycle of soil C, N and N, which can be used as early sensitive indicators of soil nutrient changes caused by climate change. To investigate the possible effects of permafrost degradation on soil enzymes in peatlands, 10 peatlands from three types of permafrost regions (sporadic island permafrost region, discontinuous island permafrost region, and continuous permafrost region) in northeast China were selected to examine the activities of soil invertase, β-glucosidase, urease and acid phosphatase and their relationships with soil physicochemical properties. The results demonstrated that permafrost type had significant effect on soil enzyme activities (P<0.001). Soil enzyme activities in discontinuous island permafrost region were significantly higher than those in sporadic island permafrost region and continuous permafrost region (P<0.05). The activities of four soil enzymes were higher in 0-15 cm than 15-30 cm soil layer. Soil enzymes were positively correlated with soil NH4+-N, SMC, TP and TN, but negatively correlated with soil NO3−-N. Soil inorganic nitrogen and moisture contents were the main factors affecting soil enzyme activities, with NH4+-N accounted for 41.6% of the variance, SMC 29.6%, and NO3−-N 11.0% (P<0.01). These results suggested that the variation in soil physicochemical properties caused by permafrost degradation might be the driving factors regulating soil enzyme activities.